Leveraging YouTube for EFL Learning: A Critical Review of Benefits, Challenges, and Pedagogical Potential - Hasan, Md. Mehedi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
With the advancement of technology worldwide, especially in education, YouTube significantly impacts language learning, particularly in English as a second language acquisition. This review enables learners to develop their English proficiency, focusing on listening and speaking skills. The purpose of this study is to investigate the importance of YouTube in enhancing English language skills, particularly listening, speaking, vocabulary, and pronunciation abilities. The research employed Braun and Clarke (2006) for thematic review, utilizing previous research from 54 peer-reviewed studies published between 2009 and 2025, which examined the effectiveness of YouTube in education. The thematic review indicates that YouTube provides learners motivation, engagement, vocabulary acquisition, improved pronunciation accuracy, and pedagogical awareness. The evaluation reveals gaps regarding support for technological literacy, instructor assistance in selecting materials, and long-term efficiency. Additionally, it emphasizes the importance of carefully incorporating YouTube into English language instruction to enhance student learning performance. This study explores the necessity of thoughtfully integrating YouTube throughout language instruction to maximize its benefits. This can significantly impact learners, aiding in their English proficiency development.